THE ROLE OF ARTIFICIAL INTELLIGENCE IN CRIMINAL JUSTICE SYSTEM (World Bulletin of Management and Law, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed the criminal justice system, revolutionizing policing, judicial processes, and evidence evaluation. AI-driven technologies such as predictive policing, facial recognition, and automated risk assessment have improved efficiency, crime detection, and decision-making accuracy. However, these developments also raise critical ethical, legal, and social concerns, including algorithmic bias, data privacy violations, lack of transparency, and the potential erosion of public trust in legal systems. The research highlights that while AI offers unparalleled potential to enhance criminal justice, its implementation requires robust regulatory frameworks, human oversight, and adherence to ethical standards to ensure fairness and protect fundamental rights. The study also emphasizes the importance of international cooperation, ongoing research, and public engagement to establish AI governance mechanisms that promote justice and accountability. Policymakers, law enforcement agencies, and judicial authorities must collaborate to harness AI’s benefits while mitigating its risks to build a criminal justice system that balances technological innovation with human rights and the rule of law